Social inequality and public health - Babones, Salvatore J.; EBSCO Publishing (Firme) (Policy Press, 2009)
Public health in the early 21st century increasingly considers how social inequalities impact on individual health, moving away from the focus on how disease relates to the individual person. This 'new public health' identifies how social, economic and political factors affect the level and distribution of individual health, through their effects on individual behaviours, the social groups people belong to, the character of relationships to others and the characteristics of the societies in which people live. The rising social inequalities that can be seen in nearly every country in the world today present not just a moral danger, but a mortal danger as well."Social Inequality and Public Health" brings together the latest research findings from some of the most respected medical and social scientists in the world. It surveys four pathways to understanding the social determinants of health: differences in individual health behaviours; group advantage and disadvantage; psychosocial factors in individual health; and, healthy and unhealthy societies, shedding light on the costs and consequences of today's high-inequality social models. This exciting book brings together leaders in the field discussing their latest research and is a must-read for anyone interested in public health and social inequalities internationally.
Keywords: Public health : Social aspects; Social medicine; Equality : Health aspects